Differentiated Methodology for Assessing the Prospects of Children in Rhythmic Gymnastics at the Initial Stage of Sports Improvement - Latpova Nigora (Genius Journals, 2023)
The article deals with the introduction into the educational and training process of the developed differentiated author's methodology for testing the motor and technical training of girls specializing in rhythmic gymnastics to determine their prospects at the initial stage of sports improvement
Keywords: differentiated methodology; training process; criterion; testing